Editorial: Defining the scope of Critical Perspectives in International Business Education Research: Frontiers in International Business Education - Šilenskytė, Aušrinė; Cordova, Miguel; Panina, Daria; Vilasboas Calixto Casnici, Cyntia; Burmester, Brent (Emerald, 2026)
Purpose The purpose of this paper is to define the scope and outline directions for research on critical perspectives in international business (IB) education. Design/methodology/approach Combining levels of higher education, curriculum components, the concept of critical perspectives and diverse approaches to IB in educational design, the editorial defines a research scope of critical perspectives in IB education. It also outlines the content of the special issue “Critical Perspectives in International Business Education: why, what, and how?” and analyzes how the papers included address identified areas of research related to critical perspectives in IB education and what future research would create value in each identified area. Findings There are four intertwined thematic layers that form the scope of research on critical perspectives in IB education, each producing many research questions to be addressed on this topic. Interaction of these four layers is an additional challenge to be explored when forming a comprehensive understanding of why, what and how to enrich IB education with critical thought. Originality/value The editorial offers a comprehensive view of areas that form research agenda on critical perspectives in IB education and therefore organizes a sporadic discussion on the topic. This helps understand the status of research in this area and meaningfully proceed with developing impactful research on the topic.
Keywords: International business; Business education; Teaching; Curriculum; Critical perspectives; fi=Strateginen johtaminen|en=Strategic Management|